Eleven Icebreaking Games Online for Distance Training Realizing ASN Free Learning - Riana Antika Amahoroe; Septri Rahayu (Jurnal Prajaiswara, 2022)
Introduction/Main Objective: The Distance Training (PJJ) pattern or blended learning has become a popular training alternative. Changes in training practices by utilizing online platforms are expected to be a means of independence for ASN in education and developing their competencies. Therefore, the instructor must adapt icebreaking, often applied in classical activities, to online icebreaking. So that PJJ can take place in a fun and meaningful way even though it is carried out virtually without involving the physical interaction of the participants. Background Problems: Icebreaking is applied in face-to-face or classical learning, but not all can be used in PJJ or online training. Widyaiswara needs an educative and interactive online icebreaking training reference. Research Method: Literature study. Novelty: This study presents 11 educational and interactive online Icebreaking games. Findings/Results: The eleven icebreaking online create an online learning atmosphere that is educative, interactive, exciting, and fun, thus creating training that is interesting, active, creative, fun, and meaningful. Eleven icebreaking fosters the interest and motivation of the training participants in the training subjects to be studied. Conclusion: Researchers believe that eleven icebreaking is an interactive and educational icebreaker that Widyaiswara can apply in online training. Glad that PJJ makes training fun and exciting, eliminates awkwardness between participants, improves concentration and focus, and creates creative and innovative activity that increases participants' learning motivation.